Inovasi Perpustakaan dalam Meningkatkan Literasi Informasi di Pesantren Darunnajah Jakarta Selatan - Ardela Dirsanala; Lolytasari Lolytasari; Muhammad Saddam Jasir (Syarif Hidayatullah State Islamic University of Jakarta, INDONESIA, 2022)
Increasing the information needs of students can be used as material for evaluating innovations for libraries in increasing the availability of information and developing the literacy skills of Islamic boarding school students. Islamic boarding schools are a gathering place for students to gain knowledge and general knowledge and religion. The purpose of this study is to explain the innovation of the Library in improving the literacy of students and the obstacles faced in efforts to increase literacy. This research uses the qualitative descriptive method. The informant determination technique that has been used is purposive sampling, which is a technique for collecting research data based on certain considerations. The informants interviewed were 3 students of Pondok Pesantren Darunnajah who took advantage of the library facilities. The results showed that the library made several innovations in meeting the information needs of students. First, the Library provides OPAC as a means of retrieving the collection information provided. Second, develop digital collections as a source of learning. In addition, pesantren set a policy to ask students to provide new books that will be served in the library, as well as cooperate with other institutions through various information training to meet the information needs of students. In addition, there is a role for literacy ambassadors who bridge the gap between the information in the library and the students. The obstacles faced are the limitation of students in obtaining access to cyber information due to the existence of a pesantren culture that prohibits students from having communication media devices in the form of cellphones and laptops personally outside the Islamic boarding school. This has caused students to have difficulties in accessing information and digital documents as those that can be part of supporting knowledge outside the Pondok